2001
DOI: 10.1046/j.0960-7692.2001.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Course and outcome of a pregnancy with a giant fetal cervical teratoma diagnosed prenatally

Abstract: We report the course and outcome of a pregnancy involving a giant fetal neck teratoma which was diagnosed at 23 weeks of gestation. Sonographic surveillance of the fetal neck revealed continuing growth of the tumor with development of polyhydramnios. Three-dimensional ultrasound provided additional detailed information on the external extent of the lesion. Color Doppler ultrasound showed intense arterial and venous flow with low resistance indices. Cesarean section under general anesthesia was planned in close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
1
17
0
3
Order By: Relevance
“…Plain X-rays and ultrasonography reveal solid and cystic structures within a heterogeneous mass with calcifications in up to 50% of cases [17][18][19][20][21][22][23][24]. The extent of vascularization can be assessed by Doppler flow imaging [25]. CT scans of the head, neck, and chest can provide more complete information regarding invasion and anatomical extension of tumor and may allow accurate reconstruction of the anatomy [26].…”
Section: Discussionmentioning
confidence: 98%
“…Plain X-rays and ultrasonography reveal solid and cystic structures within a heterogeneous mass with calcifications in up to 50% of cases [17][18][19][20][21][22][23][24]. The extent of vascularization can be assessed by Doppler flow imaging [25]. CT scans of the head, neck, and chest can provide more complete information regarding invasion and anatomical extension of tumor and may allow accurate reconstruction of the anatomy [26].…”
Section: Discussionmentioning
confidence: 98%
“…Calcifications may be seen within the mass in up to 50% of cases [4]. Rapid enlargement can be seen related to the cystic components [5].…”
Section: Discussionmentioning
confidence: 95%
“…As a result of rapid growth and expansion of a cervical teratoma, the tumor may deviate and totally occlude the trachea and esophagus, resulting in polyhydramnios due to impairment of fetal swallowing [2,3]. Polyhydramnios can be severe, requiring therapeutic amniocentesis, sometimes on multiple occasions [3,4,8]. These tumors are also known to cause fetal hydrops; the mechanism of fetal hydrops is postulated to be caused by arteriovenous shunting within the massive tumor, which leads to high output heart failure [4,9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1,[3][4][5][6][7][8] In certain cases (ie, giant melanocytic nevus with hamartoma), 6 the 3D multiplanar images were not as useful as initially expected. Those authors reported that it was hard to gain further information from the multiplanar images because of the absence of landmarks.…”
Section: Discussionmentioning
confidence: 99%